A sense of belonging contribution towards employee performance: a case in Small and Medium-sized Enterprise (SMEs) Indonesia - Rizal Afif Napitupulu; Henndy Ginting (Fakultas Seni Rupa dan Desain ITB, 2020)
Small Medium Enterprises (SME) Employees in Indonesia are relatively around 10 to 30 people. Because the number of employees just a view number, the relation between each employee is very close even like family. Even though there is an SME company in Indonesia that their employee is in line family, and because they were family, they feel belong to each other furthermore they feel a sense of belonging and become a part of the company. Feeling a sense of belonging in the workplace leads to more than just good vibes and friendships. Belonging is what allows employees to feel like they can be their authentic selves without fear of different treatment or punishment, and it has a major impact on performance and retention. From this phenomenon, this paper investigates if an employee's sense of belonging is good then it will contribute to employee performance. Employee performance has to manage because it will contribute to the productivity and effectiveness of the company. So that the company can compete with a competitor and deal with the dynamic environment. The importance of managing performance is needed for the company to adapt and compete with the competitor in any circumstances. This research prior study is to collect data and insight into employee performance based on their sense of belonging. The hypothesis of the research is a sense of belonging gives a positive influence on employee performance. The sample of the research consisted of 30 employees in one of Small Medium Enterprise (SME) in Bandung, Indonesia. A sense of belonging scale was used to collect the data. And then, data is analyzed through regression analyses with a 95% confidence interval. The regression result indicates that a sense of belonging contributes up to 69.4% of the variance towards employee's performance in Bandung SME. It means an employee with a higher sense of belonging has higher performance. Contrary, an employee with a low sense of belonging has low performance.